PENINGKATAN KEMAMPUAN GURU TAMAN KANAK-KANAK DALAM MEMANFAATKAN APLIKASI CANVA UNTUK MENDUKUNG PEMBELAJARAN - Nurdiyani, Netty; Nuryanto, Lilik Eko; Kusumastuti, Sri; Iswanti, Iswanti; Triyani, Endang (Bangun Rekaprima, 2024)
Kurikulum Merdeka (The Independent Curriculum) gives institutions/teachers the freedom to be creative in providing teaching to students. Teachers' freedom to be creative is facilitated by the government with educational platforms. Apart from that, in digital electronics, there is an application that really supports government programs. With this application, teachers and students can be creative in making interesting learning materials. The name of the application is Canva. It is used to support communicative learning , this community service activity is carried out regarding the use of the Canva application. This training was carried out at Ky Ageng Giri Kindergarten, Girikusumo Village, Banyumeneng, Mranggen, Demak. The training is aimed at kindergarten and PAUD teachers in the Ky Ageng Giri Kindergarten and its others TK surroundings. There were 15 participants who attended the training. The training steps are 1) Introduction of each service participant and audience participant, 2) explanation of the application and benefits of Canva in teaching, 3) recognizing the features in Canva, 4) practice creating various daily teaching and administration needs, 5 ) monitoring the use of Canva in school activities. The results of the training show that the participants can use this application to create posters according to the needs of each school. They can use all the elements contained in the application. Using this application requires a data package, therefore it is recommended that users first check data availability before working. Careful download of Free Canva App is also recommended because there are prepaid application.